Growth and yield of several rice varieties in swampland agroecosystems in Mesuji Regency, Lampung Province - Slameto; Meidaliyantisyah; Irawati Arfi (E3S Web of Conferences, 2021)
Swampland agroecosystem is a potential area for rice extensification program in order to increase food production. This study aimed to examine the growth and yield of several rice varieties planted in swampland agroecosystems in Mesuji Regency, Lampung Province. The experiment was conducted from November 2020 until March 2021. The planting location was in Tanjung Mas Jaya Village, Mesuji Timur District, Mesuji Regency, Lampung Province. The rice varieties planted were IAARD’s Superior varieties (Cilamaya Muncul, Inpara-2, Inpara-8, and Inpari IR Nutrizinc), multinational varieties (Mapan and Supadi) and existing local variety (Kebo). The observed variables were components of the growth and production of rice plants. The data were analyzed using Duncan test. The results showed that the yield was significantly different between the rice varieties planted. The lowest rice yield was obtained from the Inpara-2 variety (7.573 ton ha-1 of HDG). The highest yield of rice was in the Kebo variety (10.400 ton ha-1 of HDG). In order to gain optimal rice production in an area, it is necessary to use superior varieties of rice that have been adaptive to the local area.